Affirmation, Acceptance and Rejection: Polish Contemporary Documentary Filmmakers and their Relation to Poland’s Documentary Film Tradition - Katarzyna Mąka-Malatytńska (Images)
This paper attempts to define the complex attitude to the tradition in Poland of fact-driven cinema shared by members of the young generation of Polish documentary filmmakers. The examples of films by Marcin Koszałka and Wojciech Staroń, and Tomasz Wolski’s The Lucky Ones, discussed in greater detail, illustrate various shades of this complex attitude, oscillating between affirmation and opposition. The article argues against criticism that demands contemporary cinema take up certain issues and discard others.